(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: This investigation aims to evaluate pharmacotherapy utilization and adherence rates in managing diabetes mellitus and hypertension, and the association between medication adherence and pertinent patient-related factors among outpatients at Le Van Thinh Hospital in 2024. Methods: A descriptive cross-sectional study was conducted on 240 patients with hypertension, and/or diabetes mellitus for at least 12 months at Le Van Thinh Hospital between April 2024 and June 2024. Results: Regarding diabetes mellitus, metformin was the most frequently prescribed pharmacological agent (84.9%), with a common combination therapy being Biguanide + DPP- 4 inhibitor (17.6%). For hypertension, the primary pharmacological classes included calcium channel blockers (CCBs) (66.4%), beta-blockers (BBs) (64.6%), and angiotensin II receptor blockers (ARBs) (57.4%). The prevalent combination therapy was ARB + CCB + BB (17.0%). The overall medication adherence rate was 79.2%. Factors associated with medication adherence included occupation, the number of therapeutic drugs, and patients’ levels of anxiety/depression (p<0.05). Conclusion: Patient adherence to medication regimens remains suboptimal. Therefore, healthcare professionals need to focus on counseling, guiding, and promoting medication adherence through mass media channels. Patients should understand the importance of medication adherence to improve their quality of life and reduce the burden of chronic diseases.